Case report of acute abdomen caused by enterobiasis with ectopic infestation - Imad Ibrahim Ali Al-Sultan; Tarik Ibrahim Ali; O. E.Ibrahim (2011)
A case of acute abdomen with vague appendicular mass had been treated surgically. The histopathological examination of the biopsy specimen that had been taken during surgery from the appendix, greater omentum and from the lower edge of the right lobe of the liver proved to be due to Oxyuris infestation leading to a histiocytic granulomatous lesion in the omental tissue and adjacent hepatic area